EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON YIELD, YIELD ATTRIBUTING CHARACTERS AND ECONOMICS OF TURMERIC (Curcuma longa L.) var. IISR PRAGATHI - M. PADMA and S. TRIVENI, D. AMALA, B. NEERAJA PRABHAKAR (The Journal of Research, PJTSAU, 2020)
Turmeric (Curcuma longa L.) is an ancient, most valuable and sacred spice of India. It is an herbaceous,perennial belonging to the family of  Zingiberaceae. In India, it is cultivated in an area of 2,22,000 ha-1 withthe production of 10,56,000 MT. (Anon., 2016-2017).The area in Telangana under turmeric cultivation is 60,906 ha with the production of 3,77,616 MT and productivity of 6.2 t ha-1. The main turmeric growing states in Indiaare Telangana (24 %), Andhra Pradesh (22 %), Tamil Nadu (15 %), Orissa (13 %), Assam (6 %), Maharashtra (4 %), Kerala (4 %), Karnataka (3 %)and Gujarat (1 %) (Anon.,2017).